1995
DOI: 10.1007/bf00305355
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles of ?Pasteurella? piscicida: comparison with other fish pathogenic gram-negative bacteria

Abstract: The fatty acid methyl ester (FAME) profiles of "Pasteurella" piscicida were determined by gas chromatography and subjected to numerical analysis in comparison with those obtained for Vibrio anguillarum, Aeromonas salmonicida and Pasteurella species of clinical origin. The bacterial species studied shared important characteristics with respect to their FAME content: in all of them the saturated and unsaturated fatty acids of 16 carbon atoms were the predominant fatty acids. However, distinguishing features coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…All the strains tested showed cross‐reactivity against all the antisera used. In contrast, no agglutination was recorded with other related fish‐pathogenic strains of the genera Vibrio and Aeromonas ( Romalde, Magari·os, Turnbull, Baya, Barja & Toranzo 1995).…”
Section: Resultsmentioning
confidence: 95%
“…All the strains tested showed cross‐reactivity against all the antisera used. In contrast, no agglutination was recorded with other related fish‐pathogenic strains of the genera Vibrio and Aeromonas ( Romalde, Magari·os, Turnbull, Baya, Barja & Toranzo 1995).…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that P. piscicida shares major phenotypic characteristics with other fish pathogens including Vibrio anguillarum, Aeromonas salmonicida, and the clinically important pasteurellae, Pasteurella multocida and Pasteurella haemolytica [24]. A study of the fatty acid methyl ester (FAME) profiles by gas chromatography [44] revealed significant homogeneity in the major fatty acids among the different P. piscicida strains. In addition, comparison of these results with those obtained from representative strains of V. anguillarum, A. salmonicida and Pasteurella species of clinical origin suggested that the agent of fish pasteurellosis should be closer to Pasteurella than to Vibrio or Aeromonas.…”
Section: Genetic Studies and The Design Of Molecular Detection Methodsmentioning
confidence: 99%
“…piscicida strains exhibited the same morphological, biochemical and physiological characteristics. And although some variation was observed in plasmid profiling and antimicrobial resistances (Toranzo et al 1983;Magariños et al 1992;Kim and Aoki 1993a), serotyping and lipopolysaccharide, fatty acid methyl ester and outer-membrane protein profiling also demonstrated the homogeneity of this bacterum (Magariños et al 1992;Romalde et al 1995;Romalde and Magariños 1997). Recently, with the development of DNA fingerprinting techniques, new approaches have become available and have been applied to P. damselae ssp.…”
Section: Introductionmentioning
confidence: 95%